The effects of e-problem-based learning on students’ geometry problem-solving performance across Polya’s stages - Arif Abdul Haqq; Sirojudin Wahid; Nurma Izzati; Onwardono Rit Riyanto; Sulistiawati Sulistiawati; Dionisio Aquino Alves (Jurnal Elemen, 2026)
This study addresses persistent difficulties in students’ geometry problem-solving, particularly in coordinating representations and applying structured reasoning. Prior research has shown the potential of problem-based learning (PBL) and digital tools; however, limited evidence exists regarding how technology-enhanced PBL supports students’ engagement across Polya’s problem-solving stages. To examine this issue, a quasi-experimental pretest–posttest control group design was employed involving two intact undergraduate geometry classes. The experimental group was taught using e-Problem-Based Learning (e-PBL), while the control group received conventional instruction. Students’ performance was measured using a Polya-based problem-solving test. Data were analyzed using descriptive statistics, assumption testing, and an independent samples t-test. The results showed that the experimental group outperformed the control group (M = 70.74 vs. 65.07), with a statistically significant difference (p < .001) and a large effect size (d = 1.16). Performance gains were observed across all four stages of Polya’s framework, particularly in the planning and reflection stages. These findings suggest that e-PBL is associated with improved mathematical problem-solving performance by supporting structured reasoning and reflective thinking. The research emphasizes the necessity of integrating digital scaffolding and collaborative inquiry in geometry instruction.